Intelligence isn't enough : a Black professional's guide to thriving in the workplace - Anderson, Carice (Berrett-Koehler Publishers, Inc., 2022)
"Master the balance between working on your career and working in it. Intelligence Isn't Enough helps Black professionals make strategic decisions and overcome the unspoken rules for success. Recounting the despair she felt as a frustrated young Black professional, Carice Anderson knows that many Black professionals are relying on their education alone to break into the workplace. In this book, she empowers young Black professionals everywhere with the right knowledge by exposing them to advice and little-known principles of career success from her interviews with thirty successful Black leaders. Intelligence Isn't Enough is divided into six chapters that guide readers through what Anderson calls the six "major corporate muscles": IQ; Mental attitude; People matters; Cultural intelligence; Personal branding; Communication. This book includes personal stories, quotes, lessons learned, and advice from both the author and Black leaders who have worked in some of the finest institutions across North America, Africa, and Europe. Readers will learn tips and tools to strategically chart their career paths and advance in the workplace for lifelong success"--